Colombia´s Special Jurisdiction for Peace, use of Case concept within their decisions and harm to procedural guarantees - Fernanda NAVAS-CAMARGO3, Daniel Ricardo Vargas Diaz, (Opción, 2020)
Transitional Justice should provide war victims with tools that attain their dignity and leadto acknowledgement of the violations occurred, so to prevent further perpetrations of humanrights. Installment of the Special Jurisdiction for Peace (SJP)4 was made in March of year2018 and the first judgements lead to question the accuracy of their interpretation andapplication of concepts in their court decisions, i.e. Case. This paper aims to criticize thesubmission of the term, to make visible the harm being made because of wrongful applicationand breach of the procedural guarantees from international standards of judgement